Effects of marital intimacy, social support, and health status of middle-aged women on healthy aging - Lee, Hyea-Kyung (Edelweiss Applied Science and Technology, 2024)
The purpose of this study is to identify the factors affecting healthy aging among middle-aged women, focusing on marital intimacy, social support, and health status. The study participants were middle-aged women aged 40-59 residing in D city, Chungnam, and C city, Chungbuk, and 180 questionnaires were collected and analyzed. The study found that health status (β=-.273, p<.001), social support (β=.262, p<.001), lack of hobbies (β=-.199, p=.002), dissatisfaction with life (β=-.173, p=.006), having one chronic disease (β=.141, p=.020), and moderate life satisfaction (β=-.124, p=.050) were significant factors influencing healthy aging. Therefore, to promote healthy aging in middle-aged women, it is necessary to develop and apply health programs that include maintaining good health from middle age, strengthening social support, enjoying hobbies, increasing life satisfaction, and managing chronic diseases.